Strengthening Aswaja An-Nahdliyah Values in the Family: A Strategic Effort to Counter Radicalism - Ayu, Sovia Mas; Sain, Zohaib Hassan; Setiawati, Rini; Rijaya M, Okta; Hanif, Abdul (Madania: Jurnal Kajian Keislaman, 2025)
Radicalism is a central concern in the perspective of Ahlussunnah wal Jamaah (ASWAJA) as upheld by Nahdlatul Ulama. Countering radicalism can begin within the family, which serves as the primary educational institution in preparing a future generation of Muslims who are moderate and tolerant. The values of Aswaja an-Nahdliyah are internalized within the family through daily religious rituals, value habituation, and parental role modeling. This study aims to describe the implementation of Aswaja an-Nahdliyah values in family life as a strategic effort to prevent radical ideologies. Employing a qualitative phenomenological approach, the research provides descriptive insights based on participants' lived experiences. Data were analyzed through the stages of collection, reduction, presentation, conclusion, and verification. The findings indicate that the application of Aswaja an-Nahdliyah values in the family includes: (1) monotheism education (tauhid), (2) reinforcement of worship practices, (3) character development, (4) love of knowledge, (5) instilling the value of social solidarity (ukhuwah), (6) respect for tradition and local wisdom, (7) resilience and balance, and (8) empathy and compassion. It is concluded that family-based education rooted in Aswaja an-Nahdliyah values significantly contributes to the early prevention of radical ideologies. Radikalisme merupakan isu sentral dalam pandangan Ahlussunnah wal Jamaah (ASWAJA) Nahdlatul Ulama. Menangkal radikalisme dapat dimulai dari keluarga sebagai lembaga pendidikan pertama dalam mempersiapkan generasi Islam masa depan yang moderat dan toleran. Pendidikan nilai-nilai Aswaja an-Nahdiyah dalam keluarga terinternalisasi melalui aktivitas ritual keagamaan, pembiasaan nilai, dan keteladanan orang tua. Tujuan penelitian ini adalah menguraikan implementasi nilai-nilai Aswaja an-Nahdliyah dalam lingkungan keluarga sebagai strategi pencegahan terhadap paham radikal. Penelitian ini menggunakan pendekatan kualitatif fenomenologis yang menggambarkan keadaan secara deskriptif berdasarkan pengalaman hidup partisipan. Teknik analisis data dilakukan melalui tahap pengumpulan, reduksi, penyajian, penarikan kesimpulan, dan verifikasi. Hasil penelitian menunjukkan bahwa penerapan nilai-nilai Aswaja an-Nahdliyah dalam keluarga mencakup: (1) pendidikan tauhid, (2) penguatan nilai-nilai ibadah, (3) pembentukan akhlak, (4) kecintaan pada ilmu pengetahuan, (5) penanaman nilai ukhuwah, (6) penghormatan terhadap tradisi dan kearifan lokal, (7) keteguhan dan keseimbangan, serta (8) sikap empati dan kasih sayang. Dapat disimpulkan bahwa pendidikan keluarga yang berbasis nilai-nilai Aswaja an-Nahdliyah memiliki kontribusi signifikan dalam mencegah tumbuhnya paham radikalisme sejak dini.